Класифікація літературознавчих методів дослідження творчості Тоні Моррісон у західній та російській літературній критиці - Старцева, В. (Літературознавчі обрії. Праці молодих учених, 2010)
The task of the research is to analyse and classify the main literary methods of studying Toni Morrison’s creativity in Western and Russian literary criticism. There are four major methods of such studying: feminist, historical, psychoanalytic and cultural. The article deals with the central themes of Toni Morrison’s novels which are the features of Afro-American literature, its history, self| identity problems and the ways of self-searching by African-Americans.